2013
DOI: 10.1080/03632415.2013.813845
|View full text |Cite
|
Sign up to set email alerts
|

Pressures to Publish: Catalysts for the Loss of Scientific Writing Integrity?

Abstract: Publishing research is the final step in the scientific process and is used as the primary means for disseminating research findings to the scientific community. Publishing can embody many personal motivations (e.g., gratification, seeing a finished product in print, desire to further science) for authors as well as professional benefits (e.g., promotion, tenure, future funding opportunities). As the scientific workforce and competition for jobs and funding increase, publishing productivity has become a drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…A previous study testing the risk of producing retracted and corrected articles, with the latter assumed to represent a proxy of integrity, had similarly falsified the pressures to publish hypothesis as conceptualized here (16), and so did historical trends of individual publication rates (39). Therefore, cumulating evidence offers little support for the dominant speculation that pressures to publish force scientists to publish excessive numbers of articles and seek high impact at all costs (40)(41)(42). A link between pressures to publish and questionable research practices cannot be excluded, but is likely to be modulated by characteristics of study and authors, including the complexity of methodologies, the career stage of individuals, and the size and distance of collaborations (14,39,43).…”
Section: Discussionmentioning
confidence: 87%
“…A previous study testing the risk of producing retracted and corrected articles, with the latter assumed to represent a proxy of integrity, had similarly falsified the pressures to publish hypothesis as conceptualized here (16), and so did historical trends of individual publication rates (39). Therefore, cumulating evidence offers little support for the dominant speculation that pressures to publish force scientists to publish excessive numbers of articles and seek high impact at all costs (40)(41)(42). A link between pressures to publish and questionable research practices cannot be excluded, but is likely to be modulated by characteristics of study and authors, including the complexity of methodologies, the career stage of individuals, and the size and distance of collaborations (14,39,43).…”
Section: Discussionmentioning
confidence: 87%
“…A student lacking motivation is likely not going to excel. Undergraduates did rank having good field skills higher than the other choices, including "ethical," which could be a result of trying to meet the expectations and demands to compete for graduate or full-time positions (Hayer et al 2013), but as mentioned earlier the "ethical" choice in the survey was not as specifically defined as some of the other choices. Certainly, this topic warrants further discussion and should not be ignored, because ethics are an important aspect of any profession or business (Hayer et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Undergraduates did rank having good field skills higher than the other choices, including "ethical," which could be a result of trying to meet the expectations and demands to compete for graduate or full-time positions (Hayer et al 2013), but as mentioned earlier the "ethical" choice in the survey was not as specifically defined as some of the other choices. Certainly, this topic warrants further discussion and should not be ignored, because ethics are an important aspect of any profession or business (Hayer et al 2013). We also wonder whether this response reflects the message being delivered by faculty members relating to our initial question (question 1, Table 2), whereby it was indicated that field or lab experience was the most important criteria for acceptance into graduate school.…”
Section: Discussionmentioning
confidence: 93%
“…The number of published articles, the quality of the journal where they have been published, and the number of article citations are commonly used in the evaluation of scientific productivity (Hayer et al 2013).…”
Section: R Yossamentioning
confidence: 99%